Alternatives to Study Abroad: Internationalization at home as a key strategy to providing opportunities for cultural and international development. (Comparative & International Education Series, 2021)
This chapter will be based on a case study from a small college town in the northern part of the United States where students are geographically removed from interacting with people with international or diverse backgrounds. This chapter will be based on two courses: Human Geography - a general elective course aimed at freshmen students, and Population Geography aimed at junior and senior students at an institution which is located in a rather remote part of the United States.